The Effectiveness of Restorative Legal Approach in Handling Organized Crime in Indonesia - Arianty, Fitri (Journal of Adat Recht, 2025)
The restorative legal approach is an alternative method in handling crime that focuses on restoring relationships between perpetrators, victims, and the community, and prioritizes rehabilitation rather than punitive punishment. In Indonesia, where organized crime often involves complex networks and broad social impacts, this approach offers the potential to overcome challenges that exist in the conventional criminal justice system. This study aims to evaluate the effectiveness of the restorative legal approach in the context of handling organized crime in Indonesia. The research method used is qualitative, with data collection techniques through in-depth interviews with legal practitioners, law enforcement officials, and representatives of rehabilitation institutions, as well as document analysis and case studies related to the implementation of the restorative approach. The results of the study indicate that although the restorative legal approach can provide a more humanistic and constructive solution in some cases, significant challenges include resistance to change from the existing legal system, the need for training and a deeper understanding of this approach, and effective integration between restorative law and the existing criminal law system. This study suggests that in order to increase the effectiveness of this approach, there is a need for systemic reform, increased training, and the development of policies that support the implementation of restorative law in handling organized crime.